Cyberbullying di Lingkungan Sekolah: Upaya Pencegahan dan Penanganan - Cariesta, Marcelli Haura (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p12, 2025)
Cyberbullying behavior began to develop in the school environment due to the easy access to the internet among students. Quoted from Bernas.Id, Dr. Lintang Ratri Rahmiaji said that a survey from the Indonesian Internet Service Providers Association stated that out of 5,900 respondents, 49% had been victims of cyberbullying. The remaining 47.2% had never experienced bullying and 2.8% chose not to answer.  The purpose of this research is to be able to identify cyberbullying behavior in the school environment, provide prevention efforts, and handling. The research method used is descriptive qualitative in literature review and interviews. Cyberbullying in the school environment is an emotionally harmful act, carried out through various online media, and has a serious impact on both victims and perpetrators. Victims experience emotional, social, and even physical health impacts, while perpetrators can also experience psychological impacts from their actions. Prevention efforts need to involve the active role of various parties such as schools, parents, and social environment to create a safe environment from cyberbullying.